Phallocentrism of Pemmali in the Daily Conversation of People in Manorang Salo, Marioriawa Soppeng - Musyarif, Musyarif; Tami, Rosmah; Riska, Riska; Jamaluddin, Ahdar (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This study explores the phallocentric dimensions of pemmali—a traditional system of prohibitions and taboos—in the everyday conversations of the Bugis community in Manorang Salo, Marioriawa Subdistrict, Soppeng Regency. Utilizing a qualitative approach and deconstructive analysis grounded in Luce Irigaray’s concept of the symbolic order, the research examines how pemmali functions not only as a cultural moral code but also as a discursive mechanism that reinforces patriarchal norms. Data were collected through in-depth interviews and participant observation, and analyzed using a phallocentric deconstructive framework. The findings reveal that pemmali expressions frequently carry implicit gendered meanings, regulating behavior—especially of women and younger generations—under the guise of communal discipline and moral responsibility. These expressions are deeply embedded in everyday language and serve to uphold a symbolic order centered on male authority and social control. The study concludes that pemmali language constitutes a cultural product designed to maintain the Bugis cultural order, including the concept of siri, which forms a core part of the Bugis worldview. الملخص تقليدي من المحظورات والقيود — في المحادثات اليومية لمجتمع البوجيس في منطقة مانورانج سالو، مقاطعة ماروراو، محافظة سوبانغ. باستخدام نهج نوعي وتحليل تفكيكي استنادًا إلى مفهوم النظام الرمزي وفقًا لـ Luce Irigaray، تبحث هذه الدراسة كيف يعمل pemmali ليس فقط كرمز أخلاقي ثقافي، ولكن أيضًا كآلية بلاغية تعزز المعايير الأبوية. تم جمع البيانات من خلال المقابلات المعمقة والملاحظة الميدانية، وتم تحليلها باستخدام إطار تفكيكي من منظور فاليوسنتري. أظهرت نتائج البحث أن تعبيرات بيمالي غالبًا ما تحتوي على معانٍ جندرية ضمنية، والتي تتحكم في السلوك — خاصةً لدى النساء والشباب — باسم الانضباط الجماعي والمسؤولية الأخلاقية. هذه التعبيرات متأصلة في اللغة اليومية وتعمل على دعم النظام الرمزي الذي يركز على سلطة الذكور والرقابة الاجتماعية. تخلصت الدراسة إلى أن لغة بيمالي هي أحد المنتجات الثقافية التي تهدف إلى الحفاظ على النظام الثقافي البوجيسي، بما في ذلك مفهوم السيري الذي يعد جزءًا أساسيًا من نظرة المجتمع البوجيسي للعالم. Abstrak Penelitian ini mengeksplorasi dimensi falosentris (phallocentric) dari pemmali—sistem larangan dan pantangan tradisional—dalam percakapan sehari-hari masyarakat Bugis di Manorang Salo, Kecamatan Marioriawa, Kabupaten Soppeng. Dengan pendekatan kualitatif dan analisis dekonstruktif yang merujuk pada konsep symbolic order dari Luce Irigaray, penelitian ini menelaah bagaimana pemmali berfungsi tidak hanya sebagai kode moral budaya, tetapi juga sebagai mekanisme wacana yang memperkuat norma-norma patriarkal. Data dikumpulkan melalui wawancara mendalam, observasi yang dianalisis dengan pendekatan dekonstruktif falusentris. Temuan menunjukkan bahwa ungkapan-ungkapan pemmali sering memuat makna gender yang tersirat, yang mengatur perilaku—terutama perempuan dan generasi muda—atas nama kedisiplinan komunal dan tanggung jawab moral. Ungkapan tersebut tertanam kuat dalam bahasa sehari-hari dan berfungsi untuk mempertahankan tatanan simbolik yang berpusat pada otoritas laki-laki dan kontrol sosial. Studi ini menunjukkan bahwa bahasa pemali menjadi salah satu bagian dari produk budaya yang bertujuan untuk menjaga tatanan budaya termasuk siri yang menjadi pandangan dunia orang-orang Bugis.